Design, synthesis, characterization and antidiabetic evaluation of 3,5-substituted thiazolidinediones: Evidenced by network pharmacology, Molecular docking, dynamic simulation, in vitro and in vivo assessment - Shankar Gharge; Shankar G. Alegaon; Swaroop Jadhav; Shriram D. Ranade; Rohini S. Kavalapure (European Journal of Medicinal Chemistry Reports)
In search of new antidiabetic agents, heterocyclic compounds containing 3,5-Substituted thiazolidinedione moieties were synthesized through a concise three-step reaction process. The synthesis involved Knoevenagel condensation at the 5th position of the 3,5-Substituted thiazolidinedione ring-system (6a-6c). Comprehensive physicochemical and spectral analyses, including FTIR, HR-MS, 1H NMR and 13C NMR, were performed to characterize the synthesized compounds. The synthesized derivatives were subjected to evaluation for their In vivo anti-diabetic activity against diabetes induced wistar rats and In vitro activity against α-amylase, α-glucosidase and glucose uptake by yeast cells. On the basis of the combined results of network pharmacology, In vitro and animal study experiments revealed that the compounds 6c predicted to have the greatest effect out of the compounds (6a-6c), showing interactions with targets exhibited potential binding patterns against the active site of target α-amylase, α-glucosidase with modulating AMY2A, GAA, PPARG, PIK3CA, PRKCB, INSR, and PRKCB signalling pathways and this is evidenced by molecular docking, dynamics simulation (MD) studies. Further, compound 6c showed In vitro α-amylase, α-glucosidase inhibitory activity with IC50 value of 86.06 ± 1.1 μM and 74.97 ± 1.23 μM as opposed to standard acarbose (IC50 value of 26.89 ± 3.12 and 29.25 ± 0.15 μM) and 58.23 ± 0.13 % of glucose uptake and also exhibited significant reduction (p < 0.001) in blood glucose levels (114 ± 1.17 mg/dL) comparable to the effect of pioglitazone (102.2 ± 0.79 mg/dL). The present study suggests that modified thiazolidinediones act as potential lead compounds to carter the need of antidiabetic agents.